Representation of Iraqi War between Fantasy and Reality in Rajiv Joseph's Bengal Tiger at Baghdad Zoo: A New Historicist Reading - Gihan Samy Ibrahim Al Basuony (European Scientific Journal, ESJ, 2016)
Rajiv Joseph's Bengal Tiger at the Baghdad Zoo is among the plays which represent the Iraqi war— a prominent event in postmodern history. The play is based on a real story which happened in the Bagdad Zoo when some American soldiers killed a rare Bengal tiger. It is a documentation of this real story and it includes real names and historical places and characters, which make it qualified as a documentary play. The present paper employs the new historicist method in its attempt to show how much the play is a representation of the culture that motivates the actions, whether it is the culture of the author or that of the characters concerned, Arabs and Americans. Thus, the play could be seen both as a product of the interaction of the American culture and the Arab culture that it came in touch with. The American soldiers first saw this war as a mission of freedom, while the Iraqis saw it as ruin of their culture. However, the dramatic method reflects changes in perspectives as the characters come into contact. In this way, the present reading is a chance to understand cultural and intellectual history through literature and mutual influence of cultures.